Acute penile trauma and associated morbidity: 9‐year experience at a tertiary care center. (May 2015) - Phillips, Elizabeth A.; Esposito, Anthony J.; Munarriz, Ricardo
Summary: Penile fracture is an uncommon urologic emergency, defined as traumatic rupture of the tunica albuginea of the corpus cavernosum. It occurs mainly in young adults during sexual activity. In the United States, urethral injury is associated with 10–38% of all penile fractures. Diagnosis can be made clinically with the classic triad of an audible crack, detumescence, and appearance of hematoma. We sought to identify characteristics associated with true penile fracture vs. other diagnoses, and determine associated morbidity and risk factors for complications. Retrospective operative chart review identified 39 patients (mean age 39.4 years) with clinical features of penile fracture presenting to Boston Medical Center from June 2004 to May 2013. Average time from injury to presentation was 76 h (range 0.5 h–9 days) and the mechanism of injury was coital in 32 (82%) patients. Thirty‐two patients (82%) had confirmed penile fracture, 7 (18%) had isolated vascular injury. Of confirmed fractures, 4 (13%) had bilateral corporal injury and associated urethral injury. Imaging was utilized in a total of 21 cases, penoscrotal ultrasound (US) in 17 cases, retrograde urethrogram (RUG) in 3 cases, and magnetic resonance imaging (MRI) in 1 case. Penile exploration was carried out via degloving ( n  = 5, 13%) or penoscrotal ( n  = 34, 87%) incisions. At follow‐up, six patients (15%) had complications: 2 wound infections, 2 new‐onset erectile dysfunction (ED), 1 urethral stricture, 1 fistula and 1 wound dehiscence. Urethral injury increased the risk of post‐operative complications ( p  = 0.015). Penile fracture is primarily a clinical diagnosis, however imaging may be helpful if diagnosis is uncertain. Urethral injury should be suspected in cases of bilateral corporal injury and may be associated with increased morbidity. Surgical approach does not affect morbidity, but may facilitate surgical repair.